Industrial process automation systems design and implementation - Mehta, B. R.; Reddy, Y. Jaganmohan (Elsevier, 2015)
Industrial Process Automation Systems: Design and Implementation is a clear guide to the practicalities of modern industrial automation systems. Bridging the gap between theory and technician-level coverage, it offers a pragmatic approach to the subject based on industrial experience, taking in the latest technologies and professional practices. Its comprehensive coverage of concepts and applications provides engineers with the knowledge they need before referring to vendor documentation, while clear guidelines for implementing process control options and worked examples of deployments translate theory into practice with ease. This book is an ideal introduction to the subject for junior level professionals as well as being an essential reference for more experienced practitioners.
Keywords: Process control -- Automation.; Expert systems (Computer science) -- Industrial applications.; elektronické knihy; electronic books